Take Control of Interruptions in Your Life: Lessons from Routine Activity Theory of Criminology - Kalgotra, Pankush (2017)
Steeped among the items on the dark side of information technology are personal technology interruptions. Past research has examined the negative impact of technology interruptions; however, the factors that are responsible for the increasing rate of interruptions are rarely discussed. In this study, by adapting the criminology theory of Routine Activity Theory (RAT), we propose three factors that lead to an interruption: number of interruption sources, absence of guardians, and individual targetness. Results from a survey of mobile users show that combinations of these factors have increased the interruption rate in our lives. Interestingly, just having more apps on the phones does not increase interruptions; it is a combination of the factors noted above